Comprehensive Evolutionary Analysis of CPP Genes in Brassica napus L. and Its Two Diploid Progenitors Revealing the Potential Molecular Basis of Allopolyploid Adaptive Advantage Under Salt Stress - Li, Mengdi; Wang, Fan; Ma, Jiayu; Liu, Hengzhao; Ye, Hang; Zhao, Peng; Wang, Jianbo (Frontiers in Plant Science, 2022)
Allopolyploids exist widely in nature and have strong environmental adaptability. The typical allopolyploid Brassica napus L. is a widely cultivated crop, but whether it is superior to its diploid progenitors in abiotic stress resistance and the key genes that may be involved are not fully understood. Cystein-rich polycomb-like protein (CPP) genes encode critical transcription factors involved in the response of abiotic stress, including salt stress. To explore the potential molecular basis of allopolyploid adaptation to salt stress, we comprehensively analyzed the characteristics and salt stress response of the CPP genes in B. napus and its two diploid progenitors in this study. We found some molecular basis that might be associated with the adaptability of B. napus, including the expansion of the CPP gene family, the acquisition of introns by some BnCPPs, and abundant cis-acting elements upstream of BnCPPs. We found two duplication modes (whole genome duplication and transposed duplication) might be the main reasons for the expansion of CPP gene family in B. napus during allopolyploidization. CPP gene expression levels and several physiological indexes were changed in B. napus and its diploid progenitors after salt stress, suggesting that CPP genes might play important roles in the response of salt stress. We found that some BnCPPs might undergo new functionalization or subfunctionalization, and some BnCPPs also show biased expression, which might contribute to the adaptation of B. napus under saline environment. Compared with diploid progenitors, B. napus showed stronger physiological responses, and BnCPP gene expression also showed higher changes after salt stress, indicating that the allopolyploid B. napus had an adaptive advantage under salt stress. This study could provide evidence for the adaptability of polyploid and provide important clues for the study of the molecular mechanism of salt stress resistance in B. napus.